Dalilu ‘I’dadi Al Wahdat At Ta’limiyah Al Ibda’iyah Lita’allumi Al Lughah Al ‘Arabiyah - yuswandi, yuswandi; Salsabila, Octa Syakila; Kurnianto, Irawan Dwi (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2024)
In the field of education, learning modules play a strategic role as one of the mediums that enable the teaching and learning process to take place in a structured and independent manner. In the context of Arabic language learning, the development of high-quality modules is crucial to effectively support students in achieving linguistic competence. The method employed in this study is a literature review, collecting data through the exploration and analysis of various sources, such as books, journals, and previous research. The findings reveal that modules are an instructional resource that provides students with the flexibility to learn independently while also assessing their own abilities. Developing high-quality modules requires a comprehensive understanding of various related aspects. This article discusses the basic concepts of modules, their objectives, key characteristics, development principles, quality elements, components, and systematic steps in module design. The results of this study are expected to serve as a guide for module developers in creating effective and relevant teaching materials.